A Comparison of IRB and Patient Views on Consent for Research on Medical Practices - Kraft, Stephanie Alessi (Clin Trials, 2016)
BACKGROUND/AIMS: In the context of research on medical practices, which includes comparative effectiveness research and pragmatic clinical trials, empirical studies have begun to raise questions about the extent to which institutional review boards’ (IRBs) interpretations and applications of research regulations align with patients’ values. To better understand the similarities and differences between these stakeholder groups, we compare and contrast two surveys: one of IRB professionals and one of patients, which examine views on consent for research on medical practices. METHODS: We conducted online surveys of two target populations between July 2014 and March 2015. We surveyed 601 human subjects research professionals out of 1500 randomly selected from the Public Responsibility in Medicine and Research (PRIM&R) membership list (40.1% response rate), limiting analysis to the 537 respondents who reported having had IRB experience. We also surveyed 120 adult patients out of 225 approached at subspecialty clinics in Spokane, Washington (53.3% response rate). Our survey questions probed attitudes about consent in the context of research on medical practices using medical record review and randomization. The patient survey included three embedded animated videos to explain these concepts. RESULTS: A majority of IRB professionals distinguished between consent preferences for medical record review and randomization; ranked clinicians as the least preferred person to obtain participant consent (54.6%); and viewed written or verbal permission as the minimum acceptable consent approach for research on medical practices using randomization (87.3%). In contrast, most patients had similar consent preferences for research on medical practices using randomization and medical record review; most preferred to have consent conversations with their doctors rather than with researchers for studies using randomization (72.6%) and medical record review (67.0%); and only a few preferred to see research involving randomization (16.8%) or medical record review (13.8%) not take place if obtaining written or verbal permission would make the research too difficult to conduct. Limitations of our post hoc analysis include differences in framing, structure, and language between the two surveys and possible response bias. CONCLUSIONS: Our findings highlight a need to identify appropriate ways to integrate patient preferences into prevailing regulatory interpretations as IRBs increasingly apply research regulations in the context of research on medical practices. Dialogue between IRBs and research participants will be an important part of this process and should inform future regulatory guidance.